Multiple Contexts: English and Jewish Aspects of Howard Jacobson’s Novels - Szlukovényi, Katalin (Hungarian Journal of English and American Studies, 2022)
Book review:Anténe, Petr. Howard Jacobson’s Novels in the Context of Contemporary British Jewish Literature. Olomouc: Palacký University, 2019. 166 pages. ISBN 978-80-244-5651-5. Pbk. N.p.